Chlamydia in pigs: intriguing bacteria associated with sub-clinical carriage and clinical disease, and with zoonotic potential - Häcker, Georg (Frontiers in Cell and Developmental Biology, 2024)
Chlamydiae are bacteria that are intriguing and important at the same time. The genus Chlamydia encompasses many species of obligate intracellular organisms: they can multiply only inside the cells of their host organism. Many, perhaps most animals have their own specifically adapted chlamydial species. In humans, the clinically most relevant species is C. trachomatis, which has particular importance as an agent of sexually transmitted disease. Pigs are the natural host of C. suis but may also carry C. abortus and C. pecorum. C. abortus and possibly C. suis have anthropozoonotic potential, which makes them interesting to human medicine, but all three species bring a substantial burden of disease to pigs. The recent availability of genomic sequence comparisons suggests adaptation of chlamydial species to their respective hosts. In cell biological terms, many aspects of all the species seem similar but non-identical: the bacteria mostly replicate within epithelial cells; they are taken up by the host cell in an endosome that they customize to generate a cytosolic vacuole; they have to evade cellular defences and have to organize nutrient transport to the vacuole; finally, they have to organize their release to be able to infect the next cell or the next host. What appears to be very difficult and challenging to achieve, is in fact a greatly successful style of parasitism. I will here attempt to cover some of the aspects of the infection biology of Chlamydia, from cell biology to immune defence, epidemiology and possibilities of prevention. I will discuss the pig as a host species and the species known to infect pigs but will in particular draw on the more detailed knowledge that we have on species that infect especially humans.